A Rose by any Other Name: State Criminality and the Limits of Social Learning Theory - Bradshaw, Elizabeth A. (2012)
Over the past thirty years, social learning theory has emerged as one of the top criminological theories of the time. Capitalizing on Edwin Sutherland’s differential association theory, social learning theory provided the means for a quantitative assessment of Sutherland’s propositions. Advanced largely by Ronald Akers, the vast majority of research conducted on social learning theory has been limited to self-report studies of adolescents and college students, largely due to convenience. The limitations of the methods developed to empirically test social learning theory combined with the difficulty of gaining access to people in positions of power, has been the primary impediment to testing the theory’s applicability to state and corporate criminality